Archaeological Discoveries of Pre- and Proto-historic Cultures from North Kerala, South India - Ramesh N.K (Heritage: Journal of Multidisciplinary Studies in Archaeology, 2016)
This paper presents the new archaeological discoveries in Northern Kerala and seeks to situate the same in the cultural milieu of the region. An evaluation of the discoveries in light of the known record suggests the region to be occupied since the Lower Palaeolithic times